The predicting values of Pao2/Fio2 ratio in survival of neonates with Congenital Diaphragmatic Hernia - Mohamad Hadi Rafeie; Mahdi Musavi; Bahareh Ahmadi; Mehrdad Hosseinpour (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: Respiratory failure is one of the most important related factors in morbidity and mortality of neonates with congenital diaphragmatic hernia (CDH). Determining indexes that could ultimately and perceivably predict the disease severity and its prognosis is crucial. This study aimed to evaluate the predictive value of Pao2/Fio2 ratio(P/F ratio) in neonates with CDH. Materials and Methods: In this retrospective study, medical records of all neonates with CDH admitted to Alzahra (Isfahan, Iran) hospitalfrom 2005 to 2015 were checked. Thirty-five neonates with CDH were studied. Data collected were: gestational age, sex, weight, Pao2, Fio2 and clinical outcome. Results: In this survey 24 neonates with CDH were studied. The mean P/F ratio in the survival group was 2.12 ±0.90 and in the non-survival group, 1.38± 0.48. According to these results the P/F ratio in the survival group was higher than the other group and this difference was statistically significant (P= 0.02).  Based on the ROC curve, the specificity of P/F ratio in predicting survival is 72.2 percent and its sensitivity in predicting death is 80 percent. Conclusion: P/F ratio is a useful index for predicting the outcome of neonates with CDH.